Ultrasonic treatment assisted extraction of sunflower protein - I. V. Krylova; A. V. Fedorov; M. L. Domoroshchenkova; T. F. Demyanenko; L. O. Shaginova (Новые технологии, 2024)
Sunflower meal is a promising source of protein, which can be used as a food ingredient in the formulations of meat, flour and confectionery products. Alkaline extraction technology is traditionally used to obtain sunflower protein, but its efficiency can be increased using physical methods: ultrasound, microwave radiation, extraction at high pressure and others. Thу article deals with an application of the ultrasonic treatment for increase of the efficiency of protein extraction from defatted plant material: from the protein fraction of sunflower meal and from sunflower meal. The trial samples for protein extraction were prepared by the preliminary treatment of the samples in the ultrasonic bath for 15 minutes at a frequency of 40 hertz at temperature 24-28° C. The control sample was not subjected to such pretreatment. Then protein was isolated from the raw material by alkaline extraction followed by isoelectric precipitation. The possibility of the protein preparation isolation with a higher crude protein content (93,66% m.f.b) compared to the control sample has been shown. The mass yield of protein was 64% of its content in the raw material. The influence of ultrasonic treatment on the efficiency of protein extraction from raw material with different crude protein content is demonstrated. The results of the study show the feasibility of usage of ultrasound treatment in isolation of sunflower protein. In particular, the crude protein content in the trial protein sample after ultrasonic treatment was increased by 8,23% compared to the control sample. The obtained results demonstrated their consistency when compared to the results of other studies. However, there are only a limited number of studies on the use of ultrasound in the extraction of sunflower derived products.A comparison of the results obtained showed their consistency with the results of other studies. However, there are only a small number of studies on the use of ultrasound in the extraction of sunflower processing products.